30-Day Journey with Dorothy Day - Day, Dorothy, 1897-1980 (30-day journey., 2019)
Enrich each day with wisdom from our greatest spiritual thinkers. Through brief daily readings and reflections, the 30-Day Journey series invites readers to be inspired and transformed. By devoting a moment to meaningful reflection and spiritual growth, readers will find deeper understanding of themselves and the world, one day at a time. Remembered for her radical activism and dedicated life of service, Dorothy Day embodied the power of truly loving your neighbor. Whether you already admire Day or are encountering her for the first time, this journey provides the perfect way to engage the thought of one of the twentieth century's most extraordinary women.